2010
DOI: 10.1002/ppul.21236
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and atypical bacteria associated with asthma exacerbations in hospitalized children

Abstract: Children with an acute asthma exacerbation presented a high prevalence of respiratory viruses. Most hospitalizations corresponded to seasonal increases in prevalence of HRV and HRSV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
2
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 29 publications
4
34
2
8
Order By: Relevance
“…de HBoV como causa de crisis asmáticas también ha sido sugerido por algunos trabajos [26][27][28] . El antecedente de asma o sibilancias recurrentes estaba presente en alrededor de 1/3 de nuestros pacientes, tanto en los que tenían HBoV como agente único, como en los co-infectados con virus que clásicamente se presentan con sibilancias (VRS).…”
Section: Discussionunclassified
“…de HBoV como causa de crisis asmáticas también ha sido sugerido por algunos trabajos [26][27][28] . El antecedente de asma o sibilancias recurrentes estaba presente en alrededor de 1/3 de nuestros pacientes, tanto en los que tenían HBoV como agente único, como en los co-infectados con virus que clásicamente se presentan con sibilancias (VRS).…”
Section: Discussionunclassified
“…In hospitalized children aged between 3 and 16 years, HRV and HRSV were the most frequent viruses in nasopharynx secretion during asthma exacerbations (10). Similarly, a Japanese group also demonstrated that HRSV was related to wheezing episodes and was more frequent in patients with a history of asthma (11).…”
Section: The Prevalence Of Viruses In the Airwaysmentioning
confidence: 97%
“…Acute atypical bacteria are closely correlated with acute asthma attacks, and chronic MP infection plays a particularly important role in persistent asthma (Blasi and Johnston, 2007;Sutherland and Martin, 2007;Korppi, 2010;Maffey et al, 2010). An association between MP and more severe asthma exacerbation has also been observed in a previous study (Cosentini et al, 2008).…”
Section: Discussionmentioning
confidence: 99%